A Study on Students’ Learning Styles In Speaking Course At The English Department of Widya Gama Mahakam University, Samarinda - Rahmaniah; Sjamsir, Hasbi; Setiawan, Iwan (Borneo Educational Journal (Borju), 2025)
This study investigates students' learning styles in the Speaking Course at the English Department of Widya Gama Mahakam University, Samarinda. The research aimed to identify problems faced by students when using their learning styles and analyze the advantages and disadvantages of different learning styles in speaking development. The study employed a qualitative case study design with six purposively selected fourth-semester students representing visual, auditory, and kinesthetic learning styles. Data were collected through semi-structured interviews and analyzed using thematic analysis with theory triangulation for validation. For thematic analysis, we followed Braun and Clarke's six-phase framework, and for the theory triangulation, applied Fleming's VARK model. The findings revealed distinct learning style preferences that significantly influenced speaking course. Visual learners demonstrated strong preparation and organizational skills but struggled with spontaneous conversations and real-time communication. Auditory learners showed excellent listening abilities and natural speaking fluency but faced challenges with written preparation and environmental distractions. Kinesthetic learners excelled in interactive activities and experiential learning but encountered difficulties in traditional classroom settings and abstract discussions. Each learning style group faced specific challenges: visual learners experienced anxiety in unstructured speaking situations and over-dependence on visual supports; auditory learners struggled with spelling and written organization; kinesthetic learners had difficulties with sedentary learning environments. Despite their strengths, each learning style demonstrated notable limitations in comprehensive speaking development. The research contributes to understanding the relationship between learning styles and speaking skill acquisition in EFL contexts. The result is that while learning style preferences should be accommodated, students need multimodal learning strategies to overcome single-modality limitations